Quality by Design Explained: Modern Approach to Product Development - Kiran Singh; Meenu Bhatt; Nidhi Sharma; Prabhjot Singh; Surbhi Bhatt; Naveen Kumar (The Bioscan, 2025)
Regulatory bodies have given quality an important value for pharmaceutical product. The pharmaceutical industry is always looking for methods to improve and guarantee the product's quality, safety & efficacy. Quality by Design (QbD) is a modern approach for quality of pharmaceuticals. The ICH quality guidelines serve as its foundation, and its primary components are Q8 (Pharmaceutical Development), Q9 (Quality Risk Management), Q10 (Pharmaceutical Quality System), and Q11 (Development and Manufacturing of Drug Substances). It serves as a bridge between industry and drug regulatory agencies as they work toward a scientific, risk-based, holistic, and proactive approach to pharmaceutical product development. This study focuses on creating and developing formulations as well as manufacturing procedures to assure product quality within established parameters. This review article's goal is to explain how to ensure pharmaceutical quality and medication development while also discussing the idea of pharmaceutical quality by design.